Production behavior of methane hydrate in porous media using huff and puff method in a novel three-dimensional simulator - Li, Gang; Li, Xiao-Sen; Wang, Yi; Zhang, Yu (Energy, 2011)
The gas production behavior of methane hydrate in porous media using the huff and puff method was investigated in the Cubic Hydrate Simulator (CHS), a novel developed three-dimensional 5.8-L cubic pressure vessel. Three horizontal layers equally divide the CHS into four regions. A 9-spot distribution of the vertical wells, a single horizontal well and a 25-spot distribution of the thermometers are arranged on each layer, respectively. The vertical wells at the axis of the CHS were used as the injection and production wells. The huff and puff method includes the injection, soaking and production stages. The amount of water injected and produced, the gas production rate, the percentage of the hydrate dissociation and the gas-to-water ratio were evaluated. Under the thermodynamic conditions in this work, the gas production from the sediment in this work using the huff and puff method is economically profitable from the relative criterion point of view. The sensitivity analysis demonstrates the dependence of the gas production on the initial hydrate saturation, and the temperature and the injection rate of the injected hot water. (C) 2011 Elsevier Ltd. All rights reserved.